2012
DOI: 10.2478/v10168-012-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Sound Diffusers with Fabric Covering

Abstract: Fabric covering is often used by designers, as it can easily mask acoustic structures that do not match an interior. However, in the case of sound diffusers based on change in the phase of the reflected wave, the use of fabric covering is not without its effect on acoustics. It reduces the effectiveness of these structures and raises acoustic absorption. In the paper, the authors analyzed the acoustical properties of a selected fabric used to cover sound diffusers. Sound absorption and scattering coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…According to the present authors' paper [8] it is worth noting that few unpredictable problems might occur. In the case of incorrect distance between both arrays, interfering waves may disturb the frequency response in the pass band.…”
Section: Double-layer Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the present authors' paper [8] it is worth noting that few unpredictable problems might occur. In the case of incorrect distance between both arrays, interfering waves may disturb the frequency response in the pass band.…”
Section: Double-layer Arraymentioning
confidence: 99%
“…A natural step further would be to investigate the behavior of curved panels and compare frequency responses of at, convex and circle elements. One should also study fractal and wavy reector arrays or panels with diusers mounted on them [9].…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…The arrangements of seats in an auditorium is a spatial structure in that the large number of protruding edges increases the absorption of the entire auditorium as compared to the absorption capacity of a single seat. The research conducted by Pilch (2011) and Kamisiński et al (2012) on sound diffusers showed that sound absorption by spatial structures depends on their material properties and geometry, especially at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…that, averaged over the whole half-space, can be considered as the sound wave absorption coecient uniformly distributed incidence [11]:…”
Section: Introductionmentioning
confidence: 99%
“…The output acoustic impedance for the fabric hanged at a distance d 1 from a perfectly rigid wall can be expressed as [11]:…”
Section: Introductionmentioning
confidence: 99%